Riding the flume - Pfitsch, Patricia Curtis (Simon & Schuster Books for Young Readers, 2002)
In 1894, fifteen-year-old Francie determines to fight the lumbermen and protect the largest Sequoia tree ever seen, which had been given to her sister just before her death six years earlier.